Peran Orang Tua dalam Perkembangan Sosial Emosional Anak Usia Dini di PAUDQU Al Karim Mangunjaya - Rianti Rianti; Ani Suryani; Laelatul Munawaroh; Nida Nuraida; Etin Maryatin (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Social emotional development is an individual's ability to be able to adapt to their environment, both socially, namely children are able to interact and communicate with the family, school and community environment as well as emotionally, namely children are able to express and place what they feel is in them. This study aims to describe the role of parents in the social emotional development of children in PAUDQU Al Karim Mangunjaya. This research is a qualitative descriptive study with the research subjects being four children's parents. Data collection techniques used is observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. This study uses data validity tests in the form of triangulation and extension of observations. The results showed that the role of parents in the social emotional development of children is that parents act as educators, parents act as mentors, parents act as supervisors, parents act as facilitators and parents act as friends.